1986
DOI: 10.1093/nar/14.5.2201
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and nucleotide sequence of the complexAROMlocus ofAspergillus nidulans

Abstract: The AROM locus of A. nidulans, which governs five consecutive steps in pre-chorismate aromatic amino acid biosynthesis, has been cloned in a bacteriophage vector. The nucleotide sequence of the locus reveals a single, open reading-frame of 4,812 base-pairs, apparently without introns. An internal segment of the A. nidulans AROM sequence has extensive homology with the E. coli aroA gene that encodes the 5-enolpyruvylshikimate 3-phosphate synthase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 39 publications
2
90
0
Order By: Relevance
“…All the alterations are distant from the active-site lysine residue, which the experiments described in this paper identify as residue 170. The sequences of the biosynthetic 3-dehydroquinase component of A. nidulans (Charles et al, 1985(Charles et al, , 1986 and S. cerevisiae (Duncan et al, 1987) arom polypeptides are also known, and these, together with the sequence of the N. crassa peptide CNIV/T determined in the present work, may be aligned with the revised E. coli sequence as shown in Fig. 6.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…All the alterations are distant from the active-site lysine residue, which the experiments described in this paper identify as residue 170. The sequences of the biosynthetic 3-dehydroquinase component of A. nidulans (Charles et al, 1985(Charles et al, , 1986 and S. cerevisiae (Duncan et al, 1987) arom polypeptides are also known, and these, together with the sequence of the N. crassa peptide CNIV/T determined in the present work, may be aligned with the revised E. coli sequence as shown in Fig. 6.…”
Section: Discussionmentioning
confidence: 95%
“…Limited-proteolysis experiments have shown that it is possible to isolate an arom fragment that carries both the 3-dehydroquinase and shikimate dehydrogenase activities, and is similar in size and structure to the bifunctional plant enzyme (Smith & Coggins, 1983;Coggins et al, 1985). The complete sequences of two fungal biosynthetic 3-dehydroquinases, the enzymes from Aspergillus nidulans (Charles et al, 1985(Charles et al, , 1986 and Saccharomyces cerevisiae (Duncan et al, 1987), are known.…”
Section: Introductionmentioning
confidence: 99%
“…Restriction fragments of interest were cloned into phages M13mpl8 and M13mpl9 (15) and were sequenced by the dideoxy nucleotide chain-termination method and 35S-substituted adenosine 5'-[thioltriphosphate (16). Gaps in the sequence were filled in by using oligonucleotides as specific sequencing primers (17). For "compressions" in DNA sequence, 7-deaza-dGTP was used in all four sequencing reaction mixes (18).…”
Section: Methodsmentioning
confidence: 99%
“…This repressive effect is due to carbon catabolite repression rather than substrate exclusion [4]. The aromA gene encoding the pentafunctional AROM protein apparently evolved by multiple gene fusions to form a gene with a single open reading frame [5,6].…”
Section: Introductionmentioning
confidence: 99%